Comparative Assessment of Salivary Flow Rate in Tobacco Users and Non-Users by Using Modified Schirmer Test and Volumetric Method - Venkatachalam Sargurunathan, Ezhilarasi Arumugam; Pancharethinam, Durgadevi; Gowda Venkatesha, Ramachandra Reddy; Mohan, KarthikRajaram; Gokulraj, Sabitha (Journal of Neonatal Surgery, 2025)
Introduction;Saliva is an intricate bodily fluid with antifungal and antibacterial qualities that is vital to dental health and can be used as a non invasive tool in the diagnosis and prognosis of certain disease. Damage occurs in the oral cavity when salivary flow rate (SFR) decreases. Both smoke and smokeless tobacco use result in a decrease in SFR. Aimand objectives:To estimate the unstimulated salivary flow rate in tobacco smokers, chewers and non users using modified Schirmer test (MST) and volumetric method and to determine the correlation between unstimulated salivary flow rate assessed using MST and volumetric method. Materials and methods: The study population of 60 participants were divided into three groups.GroupA-20 smokers,GroupB-20 chewers, GroupC-20 Healthy individuals .The unstimulated salivary flow rate was measured using a modified Schirmer test for 3min and a volumetric method for 5 min. Results: A significant positive correlation was observed between the SFR value obtained by the modified Schirmer test and the volumetric method (GROUP A p=0.008,GROUP B p=0.002). The salivary flow rate assessed using MST shows there was a decrease in salivary flow rate in smokers and chewers when compared to control group in 1st,2nd and third minute. Conclusion: Modified Schirmer Test (MST) can be used as an effective alternative non-invasive tool to estimate Salivary Flow Rate (SFR